The correlation between primary ovarian insufficiency, sex hormones and immune cells: a two-step Mendelian randomization study - Hong, Tongtong; Pu, Danhua; Wu, Jie (Frontiers in Endocrinology, 2025)
BackgroundPrimary ovarian insufficiency (POI), a cause of female infertility, is characterized by elevated gonadotropin levels and fluctuating estrogen reductions, accompanied by irregular menstruation, osteoporosis, cardiovascular disease, and genitourinary syndrome of menopause. Previous studies have shown an association between POI and immune cells, but the causal relationship remains unclear. Sex hormones play a crucial role in immune regulation by influencing the function and levels of immune cells, suggesting they may be key mediators between POI and immune cells.MethodsUtilizing genome-wide association studies (GWAS), we conducted a comprehensive bidirectional two-sample Mendelian randomization (MR) analysis to explore the causal relationship between 731 immune cell traits and POI. Furthermore, a two-step MR analysis was employed to examine the potential mediating effects of sex hormones between these two systems. To ensure the robustness of our findings, we performed extensive sensitivity analyses, evaluating heterogeneity and horizontal pleiotropy.ResultsAfter FDR adjustment (PFDR < 0.05), ten immune cell phenotypes were significantly correlated with the risk of POI. Among these, one immune cell phenotype was identified as a risk factor for POI (OR > 1), while the other nine immune cell phenotypes were protective factors (OR < 1). In the reverse MR analysis, POI was positively correlated with seven immunocyte phenotypes (OR > 1) and negatively correlated with eleven immunocyte phenotypes (OR < 1). No potential mediating effects of ten sex hormones were found between POI and immune cell traits.ConclusionsOur study comprehensively assessed the correlation between immune cell phenotypes and POI in the European population, excluding the mediating role of sex hormones, thus providing valuable insights into the biological mechanisms of POI and informing early prevention and treatment strategies.